PENGARUH VARIASI SNP TERHADAP RISIKO KEJADIAN MENINGIOMA: SEBUAH TELAAH SISTEMATIS DAN META ANALISIS - Elvan Wiyarta (PERDOSNI, 2022)
Meningiomas are the most common type of extraaxial intracranial neoplasm. Along with the development of genomics, several studies have begun to examine the association of meningioma occurrence with the presence of single-nucleotide polymorphisms (SNPs). This study aims to examine the relationship between SNP and the risk of meningioma. Literature searches were carried out on various databases which were then collected, reviewed, and assessed for eligibility criteria. From the search results, obtained 7 studies to be analyzed statistically. The results of grouping these studies showed that 3 SNPs (rs1801133, rs1805087, and rs4968451) in 3 genes (MTHFR, MTR, and BRIP1) were associated with meningioma risk. Of the 3 SNPs, only rs1801133 aa had a significant association with meningioma risk (pooled OR [95%CI]: 2.32 [1.34-4.02]). This shows that mutations in the MTHFR gene in the SNP rs1801133 in both alleles (aa) cause a person to have a 2.32 times greater risk of developing meningioma than people who do not have this SNP. Keyword: meningiomas; SNPs; genome-wide association study; risk factors; bioinformatics